Application of a conversion electrode based on decomposition derivatives of Ag4[Fe(CN)6] for aqueous electrolyte batteries. Issue 16 (29th March 2022) - Malchik, Fyodor; Maldybayev, Kaiyrgali; Kan, Tatyana; Kokhmetova, Saule; Kurbatov, Andrey; Galeyeva, Alina; Tubul, Nufar; Shpigel, Netanel; Djenizian, Thierry
Abstract : The lack of stable electrode materials for water-based electrolytes based on intercalation and conversion reaction mechanisms encourage scientists to design new or renovate existing materials with better cyclability, capacity, and cost-effectiveness. Abstract : The lack of stable electrode materials for water-based electrolytes due to the intercalation and conversion reaction mechanisms encourage scientists to design new or renovate existing materials with better cyclability, capacity, and cost-effectiveness. Ag4 [Fe(CN)6 ] is a material belonging to the Prussian blue family that can be used, as its other family members, as an electrode material with the intercalation/deintercalation reaction or conversion-type mechanism through Ag oxidation/reduction. However, due to the instability of this material in its dry state, it decomposes to AgCN and a Prussian blue residual complex. A possible reason for Ag4 [Fe(CN)6 ] decomposition is discussed. Nevertheless, it is shown that the decomposition products of Ag4 [Fe(CN)6 ] have electrochemical activity due to the reversible oxidation/reduction of Ag atoms in water-based electrolytes.